ANALISIS PENGARUH PERIKLANAN DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN MEMBELI PRODUK SARIMI INSTAN STUDI KASUS DI KOTA PEKALONGAN - Shofiyuddin, Muhammad (Majalah Neraca, 2012)
This research entiled âThe Influence of Analysis Advertising and Product Attribute toward Purchasing Decisions Sarimi Â Instan Product on Pekalongan City. The aim of this research is to know and to analyze the influence of availability advertising and product attribute sarimi instan product toward purchasing decisions either partially and simultanously. The data which be used are the primer (using questionary) and secondary data, based on accindental sampling method and purposive sampling Method. Â This research used validity test and reability test, then analyze using multiple regression tehnique to test the hypothesis with F test and t test. The result of the research showed that availability is significant influence variable advertising and product attribute sarimi instan product toward purchasing decisions either partially or simultanously, while the purchasing decisions the product sarimi instan can be explained by variable advertising and product attribute is 99 %.Keyword : advertising, product attribute, purchasing decisions.